THE INFLUENCE OF CAPITAL ADEQUACY RATIO, NET INTEREST MARGIN AND OPERATIONAL COSTS OF OPERATING REVENUE ON RETURN ON ASSET WITH LOAN TODEPOSIT RATIO AS INTERVENING VARIABLE - Sri Puji Lestari; Sri Fitri Wahyuni; Wido Seno Affandi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Research Problems: To further increase the existence of conventional banks and the trust of the Indonesian people in conventional banking services, it is necessary to improve the performance of conventional banking. The problems in this study are whether CAR, NIM, BOPO and LDR have a significant effect on ROA; Do CAR, NIM, and BOPO have a significant effect on LDR; and whether CAR, NIM and BOPO have a significant effect on ROA through LDR as an intervening variable. Research purposes: To find out how much influence CAR, NIM, BOPO and LDR have on ROA; to find out how much influence CAR, NIM, and BOPO have on LDR; and to find out how much influence CAR, NIM and BOPO have on ROA through LDR as an intervening variable. Research methods: This type of research is quantitative research with a descriptive approach. The object of this research is a commercial bank listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The sample in this study was 10 conventional commercial banks, which were selected based on the purposive sampling method. Data analysis technique using multiple linear regression analysis. Research Findings: Partially there is no significant effect of the CAR variable on the LDR, there is a significant negative effect of the NIM variable on the LDR; and there is a significant positive effect of BOPO on LDR; there is an insignificant negative effect of the CAR variable on ROA, there is a significant positive effect of the NIM variable on ROA, there is no significant effect of the BOPO and LDR variables on ROA. Simultaneously CAR, NIM, BOPO have a positive and significant effect on LDR and CAR, NIM, BOPO and LDR have a positive and significant effect on ROA. LDR is the intervening variable of CAR on ROA, because the number of direct effects of CAR on ROA is smaller, but LDR is not an intervening variable of NIM and BOPO on ROA because the number of direct effects of NIM and BOPO on ROA is greater than the indirect effect.